Educational achievement in Japan : - Lynn, Richard (Macmillan Press in association with the Social Affairs Unit, 1988)
Educational standards in Japan are the highest in the world. In this first comprehensive study of these standards Professor Richard Lynn concludes that Japanese teenagers are about two years ahead of their contemporaries in Europe and the United States. At a time when there is much public disquiet about low educational standards in Europe and the United States, this book should be read by everyone concerned with education in the West